Microalgae: Antiquity to era of integrated technology. (May 2017) - Patel, Akash; Gami, Bharat; Patel, Pankaj; Patel, Beena
Abstract: Uncontrolled anthropogenic activities and technological revolution increase fossil fuel consumption at higher rate that prompted researchers looking for alternative energy source to cover the current need and future demand of energy. Biomass of terrestrial crops has been studied as a promising source of renewable energy in last few decades however large scale production is still questionable because of lower productivity, indirect use of fossil fuel, lack of land availability and food vs. fuel conflict. These limitations of land based system fetch opportunity to look into untapped potential use of microalgae with high biomass productivity from saline and waste water stream. This unconventional way of feedstock generation can additionally produce value added products apart from clean energy. This review presents current scenario of microalgae applications in biofuel production and micro algae based high value bio-product industries leveraging environmental protection and waste utilization benefits. Microalgae cultivation, harvesting and biomass conversion technologies for biodiesel production have been reviewed based on adapting ancient learning to understand critical factors affecting overall productivity and economic viability. Dedicated efforts from technical experts are still required for economic viability of large scale biodiesel production in spite of positive finding at small scale. Several high value bio-products from microalgae amplified magnetism of trades for investment in this field. Microalgae cultivation intersects two key concern areas of global warming and water pollution control/water recycling by CO2 sequestration and waste water utilization respectively. Integration of suitable upstream and downstream processing technologies with multiple product portfolio would make the microalgae bio-refinery economical viable.